2018
DOI: 10.1002/dneu.22660
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to Psychostimulant Primes Activity‐dependent Gene Induction in Frontal Cortex

Abstract: Perinatal neurodevelopment involves extensive formation of neural connections and onset of activity-dependent gene expression for synaptic function and plasticity. Exposure to psychostimulants at this stage imposes significant risks for developing cognitive and affective disorders later in life. However, how developmental exposure to psychostimulants may induce long lasting molecular changes relevant to neural circuit function remains incompletely understood. In this study, we investigated the impacts of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In that study, Arc (an immediate early gene that responds to neuronal activation) was used as a reporter to show the priming effect of amphetamine for rapid and persistent enhancement of histone monomethylation (H3K4me1). The results suggest that developmental exposure to psychostimulants induces long‐lasting changes to chromatin, which can still enhance neuronal responses at later stages even in the absence of psychostimulants, and also suggests how early exposure to psychoactive and addictive drugs increase the risk of psychiatric disorders (Ye et al ., ).…”
Section: Environmental Factors and Epigenetic Controlmentioning
confidence: 97%
See 1 more Smart Citation
“…In that study, Arc (an immediate early gene that responds to neuronal activation) was used as a reporter to show the priming effect of amphetamine for rapid and persistent enhancement of histone monomethylation (H3K4me1). The results suggest that developmental exposure to psychostimulants induces long‐lasting changes to chromatin, which can still enhance neuronal responses at later stages even in the absence of psychostimulants, and also suggests how early exposure to psychoactive and addictive drugs increase the risk of psychiatric disorders (Ye et al ., ).…”
Section: Environmental Factors and Epigenetic Controlmentioning
confidence: 97%
“…Epigenetic regulation is likely to be involved in such long-lasting effects. Indeed, Ye and colleagues demonstrated that amphetamine treatment enhances neuronal activity in response to immediate stimulation, as well as subsequent stimulation without amphetamine treatment (Ye et al, 2018). In that study, Arc (an immediate early gene that responds to neuronal activation) was used as a reporter to show the priming effect of amphetamine for rapid and persistent enhancement of histone monomethylation (H3K4me1).…”
Section: Environmental Factors and Epigenetic Controlmentioning
confidence: 99%
“…Images were processed using a custom-written MATLAB (MathWorks) script with three subfunctions-one for detecting axons in the red channel of BLA images, one for detecting boutons in the green channel of BLA images, and one for detecting cells in both the red and green channels of VTA images. The axon detection function used Hessian filters to highlight line-like structures in the photomicrographs [56][57][58], and the filtered images were thresholded at 5 standard deviations (10× Olympus images) or 7 SD (25× Zeiss images) above image background in accordance with visual inspection. The detected line segments were then skeletonized to one pixel-width, so total pixel output would represent axon length.…”
Section: Image Analysismentioning
confidence: 99%